2012
DOI: 10.1007/s12291-012-0208-9
|View full text |Cite
|
Sign up to set email alerts
|

To Establish the Reference Intervals of Lipid Profile in Punjab

Abstract: Overnight fasting samples of 1,031 apparently healthy people of Punjab visiting the hospital over a period of 3 years were tested for serum lipid profile. The mean ± SD of serum total cholesterol, triglycerides, high density lipoprotein cholesterol, low density lipoprotein cholesterol and very low density lipoprotein cholesterol in mg/dl were 182.2 ± 33.9, 122.4 ± 33.4, 44.1 ± 6.8, 113.9 ± 32.0, 24.6 ± 7.1 respectively. When these subjects were grouped according to age and sex, no appreciable difference was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 16 publications
5
13
3
Order By: Relevance
“…Recent studies from different geographical locations of India have established reference intervals for certain biochemical parameters and also identified significant changes in liver markers and lipid levels in healthy Indian population [16][17][18][19][20][21]. Furthermore, we have documented that the renal and cell integration markers like creatinine, AST and GGT were lower in females than males as supported by previous studies done elsewhere [22,23].…”
Section: Discussionsupporting
confidence: 84%
“…Recent studies from different geographical locations of India have established reference intervals for certain biochemical parameters and also identified significant changes in liver markers and lipid levels in healthy Indian population [16][17][18][19][20][21]. Furthermore, we have documented that the renal and cell integration markers like creatinine, AST and GGT were lower in females than males as supported by previous studies done elsewhere [22,23].…”
Section: Discussionsupporting
confidence: 84%
“…To the best of our knowledge, this is the first ever large study providing representative age and gender specific percentile values for serum lipids, glucose, blood pressure, and BMI in healthy Gujarati Indians. Contrary to earlier reports where no substantial sex specific difference was noted in the lipid profile [ 11 , 25 ], we had obtained significant difference between the risk profiles of males and females of the study population. The females were having superior CVD risk factor profile due to the estrogenic protective effect, which was found to be lost in the 5th to the 6th decade of life.…”
Section: Discussioncontrasting
confidence: 99%
“…Mean body mass index, systolic/ diastolic blood pressure, fasting blood glucose and triglyceride levels in our study have been found to be similar to that reported by other studies, [ 31 , 34 ] but mean total cholesterol levels were lower than earlier reported in literature. [ 24 , 36 38 ] No recent population based study reporting mean levels of cholesterol lipoproteins and prevalence of various dyslipidemias in Punjab could be found.…”
Section: Discussionmentioning
confidence: 99%